2010
DOI: 10.1007/s13181-010-0050-5
|View full text |Cite
|
Sign up to set email alerts
|

A Localizing Circumferential Compression Device Delayed Death After Artificial Eastern Diamondback Rattlesnake Envenomation to the Torso of an Animal Model in a Pilot Study

Abstract: Nearly all prior studies to delay onset of systemic toxicity and death after snake bite use a model of distal extremity envenomation. In the first of a series of planned studies using snake venoms with different toxicity profiles, the application of a novel device in a new model of torso envenomation in the setting of Eastern Coral Snake (Micrurus fulvius) venom (a potent neurotoxin) envenomation showed promise by delaying systemic intoxication. In this pilot study, we investigated this novel localizing circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…The early work by Sutherland included studies on the effects with pitviper venoms such as Crotalus adamanteus and did show a delay in the development of systemic effects and yet with less local swelling [ 139 ]. These results are congruent with the above C. atrox study [ 138 ] as well as research by another group that showed a delay in C. adamanteus lethal effects [ 140 ] and another that showed delay in venom absorption but without an increase in swelling [ 141 ]. None of these laboratory-based studies reported upon the relative necrotic effects, likely due to the short-time periods for which the studies were conducted.…”
Section: Issues and Controversies In Modern Medical Caresupporting
confidence: 92%
“…The early work by Sutherland included studies on the effects with pitviper venoms such as Crotalus adamanteus and did show a delay in the development of systemic effects and yet with less local swelling [ 139 ]. These results are congruent with the above C. atrox study [ 138 ] as well as research by another group that showed a delay in C. adamanteus lethal effects [ 140 ] and another that showed delay in venom absorption but without an increase in swelling [ 141 ]. None of these laboratory-based studies reported upon the relative necrotic effects, likely due to the short-time periods for which the studies were conducted.…”
Section: Issues and Controversies In Modern Medical Caresupporting
confidence: 92%
“…It is suggested that they be considered as adjunct first aid to mechanical methods such as PBI (a snakebite first aid recommended by the Australian National Health and Medical Research Council), which while highly effective for limb bites are often incorrectly applied [10] . The topical agents might also be useful for bites to the torso and hence might be used as adjuncts to the local pressure pad with compression approach, which as indicated from animal studies is effective even for such bites [7] . Our previously reported findings for NO releasing ointment [13] indicate that a reasonable approach would be to apply an ointment formulation of the inhibitor just above the bite site.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, the only formally accepted snakebite first aid is pressure bandaging with immobilization (PBI) [3] , [4] . Local pressure pad with compression, another mechanical method, is also seen as a potentially useful first aid [5] , [6] , [7] . PBI, which has long been endorsed by the National Health and Medical research Council of Australia against bites from Australian snakes, aims to limit venom entry into the circulation by preventing lymphatic transport without inhibiting arterial or venous blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…Since pressure immobilization bandages could not be used for bites on the torso, consideration was given to a circumferential compression device consisting of a ring with two hooks for attaching a band to apply pressure ( Figure 3 ). This device was tested in the porcine model for experimental torso envenomations for both eastern coral snake ( Micrurus fulvius fulvius ) [ 30 ] and eastern diamondback rattlesnake [ 31 ].…”
Section: Methodsmentioning
confidence: 99%